Anemia and Micronutrient Status during Pregnancy, and Their Associations with Obstetric and Infant Outcomes among HIV-Infected Ugandan Women Receiving Antiretroviral Therapy. Issue 5 (25th April 2020) - Finkelstein, Julia L; Herman, Heather S; Plenty, Albert; Mehta, Saurabh; Natureeba, Paul; Clark, Tamara D; Kamya, Moses R; Ruel, Theodore; Charlebois, Edwin D; Cohan, Deborah; Havlir, Diane; Young, Sera L
ABSTRACT: Background: Women living with HIV (WLHIV) are at higher risk of micronutrient deficiencies and adverse health outcomes. There are limited data on the burden or sequelae of micronutrient deficiencies among pregnant WLHIV receiving antiretroviral therapy (ART). Objectives: We aimed to examine anemia and vitamin B-12, folate, and vitamin D deficiencies, and their associations with obstetric and infant outcomes, among pregnant WLHIV initiating combination antiretroviral therapy (cART) in rural Uganda. Methods: This was a prospective analysis among pregnant WLHIV (12–28 weeks of gestation) in PROMOTE-Pregnant Women and Infants (PIs), a randomized trial comparing the effects of protease inhibitor (PI)-based ART with those of a non-PI-based ART on placental malaria risk. We conducted a substudy on the burden of anemia [trimester 1/3: hemoglobin (Hb) <11.0 g/dL; trimester 2: Hb <10.5 g/dL; n  = 367] and micronutrient deficiencies ( n  = 127) in pregnant WLHIV and their associations with obstetric and infant outcomes. Hb was measured by cyanmethemoglobin, vitamin B-12 and folate were measured via electrochemiluminescence, and vitamin D was measured by ELISA. Linear and binomial regression were used to evaluate associations between micronutrient status during pregnancy and perinatal outcomes. Results: 26.8% women were anemic, 30.2% were vitamin B-12 insufficient (<221.0 pmol/L), 66.1% were folate insufficient (<13.5 nmol/L), and 65.4% were vitamin D insufficient (<30.0 ng/mL) at enrollment. Anemia during pregnancy was associated with a greater risk of small for gestational age (SGA) (RR: 1.88; 95% CI: 1.28, 2.77; P  = 0.001); each 1-g/dL decrease in Hb was associated with greater risk of SGA (RR: 0.76; 95% CI: 0.65, 0.90; P  = 0.001). Multivariate models showed that increased vitamin D concentrations predicted lower risk of infant wasting (WLZ < −2; RR: 0.94; 95% CI: 0.89, 0.99; P  = 0.04). Multivariate models also indicated that maternal vitamin B-12 and folate concentrations at enrollment predicted maternal ( P  < 0.001) and infant ( P  = 0.02) concentrations postpartum. Conclusions: Anemia and micronutrient deficiencies are associated with a variety of adverse obstetric and infant outcomes and are an important public health concern in perinatal WLHIV on cART and their children. This trial was registered at clinicaltrials.gov as NCT00993031. Abstract : Anemia and micronutrient deficiencies were common among perinatal Ugandan women living with HIV and initiating combined antiretroviral therapy, as well as their infants. Lower hemoglobin, folate, vitamin D and vitamin B12 deficiencies were associated with a variety of adverse obstetric and infant outcomes. These data suggest micronutrient deficiencies likely remain an important public health concern for vulnerable populations, even in the era of combined antiretroviral therapy.